Improving learning outcomes through the Teaching Through Problem Solving (TTP) Approach for Class VI students at SDN Lidah Wetan II/462 Surabaya.: Improving learning outcomes through the Teaching Through Problem Solving (TTP) Approach for Class VI students at SDN Lidah Wetan II/462 Surabaya. - Lestari, Risa Puji (Universitas Nahdlatul Ulama Pasuruan, 2022)
Lestari, Risa Puji. 2022. Improving learning outcomes through the Teaching Through Problem Solving (TTP) Approach for Class VI students at SDN Lidah Wetan II/462 Surabaya. Contextual learning process is able to provide meaningful learning. This learning motivates students to have the ability to solve problems. This requires teachers to have appropriate teaching methods so that students can learn actively and are able to understand learning materials and think critically. One of the steps that must be taken is the application of learning through the Teaching Through Problem Solving (TTP) approach. However, in the observations made by the author, there are still learning that has not been able to provide meaningful learning, so students have not been able to understand the material well and there are still many students who score below the KKM. This study aims to describe the application of learning through the Teaching Through Problem Solving (TTP) approach and improving the learning outcomes of class VI students. The results showed that student learning outcomes increased. At the stage before the improvement there were only 10 of 33 students or 30% who experienced mastery learning, increased to 20 of 33 students or 61% who experienced completeness in the first cycle, and experienced a significant increase to 29 of 33 students or 87% of students who experienced completeness in cycle II, and classically has fulfilled learning mastery which is more or equal to 85% of students who complete. So in conclusion, the application of learning through the teaching trough problem solving approach to class VI students of SD Negeri Lidah Wetan II/462 Surabaya in the 2021/2022 academic year can improve student learning outcomes. Keywords: teaching through problem solving approach, learning outcomes.